Initial Validation and Reliability of the CDKL5 Deficiency Disorder Hand Function Scale (CDD-Hand). (May 2022) - Saldaris, Jacinta; Leonard, Helen; Jacoby, Peter; Marsh, Eric D.; Benke, Tim A.; Demarest, Scott; Downs, Jenny
Pathogenic variants in the CDKL5 gene result in CDKL5 deficiency disorder (CDD), which is characterized by early-onset epilepsy, severe developmental delay, and often, cortical visual impairment. Validated clinical outcome measures are needed for future clinical trials to be successful. This study aimed to adapt the Rett Syndrome Hand Function Scale for CDKL5 deficiency disorder and evaluate its feasibility, acceptability, content validity, and reliability. Consultation with a cortical visual impairment experienced specialist and the Consumer Reference Group informed modifications to the instructions of the Rett Syndrome Hand Function Scale for children with CDKL5 deficiency disorder (CDD-Hand). Eighty-six families registered with the International CDKL5 Disorder Database provided video clips of their child's hand function and provided feedback about the measure. Video data were coded by 2 researchers to evaluate intra- and interrater reliability. This study provides initial evidence of validation and reliability. The scale appears to be suitable for a range of ages and functional abilities for CDKL5 deficiency disorder.